2016
DOI: 10.18632/oncotarget.12814
|View full text |Cite
|
Sign up to set email alerts
|

Low dose angiostatic treatment counteracts radiotherapy-induced tumor perfusion and enhances the anti-tumor effect

Abstract: The extent of tumor oxygenation is an important factor contributing to the efficacy of radiation therapy (RTx). Interestingly, several preclinical studies have shown benefit of combining RTx with drugs that inhibit tumor blood vessel growth, i.e. angiostatic therapy. Recent findings show that proper scheduling of both treatment modalities allows dose reduction of angiostatic drugs without affecting therapeutic efficacy. We found that whilst low dose sunitinib (20 mg/kg/day) did not affect the growth of xenogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
(66 reference statements)
3
28
0
1
Order By: Relevance
“…Thus, improved tumor perfusion might represent an additional mechanism of radiotherapy-induced tumor oxygenation, next to previously described mechanisms like decreased oxygen consumption, increased inflammation and reduced tumor volume [55]. While the improved perfusion and oxygenation might increase the efficacy of subsequent irradiations, our recent findings confirm that the tumor areas with increased perfusion also contained more viable tumor tissue [28]. Apparently, the improved tumor vascularization and oxygenation can also contribute to tumor cell survival or to tumor regrowth following fractionated radiotherapy.…”
Section: The Rationale Behind Combining Angiostatic Drugs With Radiotsupporting
confidence: 68%
See 1 more Smart Citation
“…Thus, improved tumor perfusion might represent an additional mechanism of radiotherapy-induced tumor oxygenation, next to previously described mechanisms like decreased oxygen consumption, increased inflammation and reduced tumor volume [55]. While the improved perfusion and oxygenation might increase the efficacy of subsequent irradiations, our recent findings confirm that the tumor areas with increased perfusion also contained more viable tumor tissue [28]. Apparently, the improved tumor vascularization and oxygenation can also contribute to tumor cell survival or to tumor regrowth following fractionated radiotherapy.…”
Section: The Rationale Behind Combining Angiostatic Drugs With Radiotsupporting
confidence: 68%
“…Despite this apparent conflict, several preclinical studies have shown that angiostatic treatment can enhance tumor oxygenation, thereby increasing the efficacy of radiation treatment [13, 22, 26–28]. The mechanisms by which angiostatic drugs improve tumor oxygenation are still not fully understood.…”
Section: The Rationale Behind Combining Angiostatic Drugs With Radiotmentioning
confidence: 99%
“…Using dynamic contrast-enhanced MRI and contrast-enhanced ultrasonography, we recently also observed increased tumor perfusion following two weeks of fractionated irradiation in a xenograft mouse tumor model. This was accompanied by reduced intratumoral hypoxia and increased tumor viability (35). Of note, increased tumor oxygenation during radiotherapy has been linked to different mechanisms, such as decreased oxygen consumption and vasorelaxation via increased inflammation (36).…”
Section: Radiotherapy and The Tumor Vasculaturementioning
confidence: 99%
“…Other data [12, 15] suggest that giving RT before sunitinib allowed a dose reduction in sunitinib, while maintaining a comparable antitumor effect.…”
Section: Resultsmentioning
confidence: 99%